Measurement of CP-violating and mixing-induced observables in B0s→[phi] γ decays - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review letters, 2019)
A time-dependent analysis of the B-s(0) -> phi gamma decay rate is performed to determine the CP -violating observables S-phi gamma and C-phi gamma and the mixing-induced observable A(phi gamma)(Delta). The measurement is based on a sample of pp collision data recorded with the LHCb detector, corresponding to an integrated luminosity of 3 fb(-1) at center-of-mass energies of 7 and 8 TeV. The measured values are S-phi gamma = 0.43 +/- 0.30 +/- 0.11, C-phi gamma = 0.11 +/- 0.29 +/- 0.11, and A(phi gamma)(Delta) = -0.67(-0.41)(+0.37) +/- 0.17, where the first uncertainty is statistical and the second systematic. This is the first measurement of the observables S and C in radiative B-s(0) decays. The results are consistent with the standard model predictions.
R. Aaij, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, P. d’Argent, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, H. Malygina, J. Marks, S. Neubert, A. Piucci, N. Skidmore, U. Uwer, J. van Tilburg, A. Zhelezov [und weitere] (LHCb Collaboration)
Gesehen am 18.12.2019
im Text werden phi und gamma als griechische Zeichen dargestellt